Effect of Cyanobacteria-Enriched Compost on Maize (Zea mays. L) Growth and Yield and Nutrient Uptake in Inceptisols - Trias Oktaviyani; Tamad Tamad; Jati Purwani (JOURNAL OF TROPICAL SOILS, 2024)
Increased production of food crops has various obstacles, including soil fertility, which is also caused by the price of inorganic fertilizers, which is burdensome for farmers. Organic and biofertilizers can reduce the use of inorganic fertilizers and the level of degradation of soil fertility. The research was conducted in the greenhouse of Indonesia Soil Research Institute in Bogor from October 2021 to March 2022. The treatments were laid out in a randomized block design consisting of 12 treatments with three replications, consisting of level doses of NPK combined with compost, cyanobacteria, and (Cyanobacteria-enriched compost). (NPK75%+compost) treatment gave the highest corn cobs and grain yield by 209.86 g plant-1 (8.55%) and 163.49 g plant-1 (6.42%), respectively compared to NPK100%. The treatment of  (NPK75%+compost) gave a similar grain yield with 100% NPK and can scale down  NPK used by 25%. (NPK50%+cyanobacteria-enriched compost) treatment increased N uptake by 48.81% compared to NPK100%. The treatment of (NPK50%+cyanobacteria-enriched compost) increased P uptake by 0.8 mg plant-1 or 17.0% compared to NPK50%+compost. At NPK50%+cyanobacteria, K uptake increased by about 31.46% compared to NPK50%.